Effects of residual speech and auditory deprivation on speech perception of adult cochlear implant recipients - ÇİPRUT, AYŞE AYÇA; GEÇİCİ, CENNET REYYAN; AKDENİZ, ESRA; YÜKSEL, MUSTAFA (ELSEVIER SCI LTD, 2019)
Objective: Possible predictive factors of cochlear implant (CI) outcomes have been extensively reported in literature for different user groups such as prelingual pediatric or postlingual adult users. However, there remains unexplained outcome variability among adult CI users; therefore, research concerning these patients continues and many different variables have been reported. This study aimed at evaluating the relationship between preoperative speech reception capacity, residual hearing, duration of deafness, age of implantation, and postoperative monosyllabic word recognition scores (WRSs) in postlingual CI users. Methods: Effect of onset age of hearing loss, duration of hearing loss, cochlear implantation age, pre CI speech reception thresholds (SRT) and pre CI WRS on the post-CI WRS of 76 adults were analyzed. Results: There are statistically significant relationships between hearing loss duration, pre-CI WRS, residual hearing and the post CI WRS. We observed that patients with shorter auditory deprivation with measurable speech perceptions and residual hearing might perform better with CI. Conclusion: Ear selection in cases of unilateral CI should be considered on an individual basis with respect to the speech perception abilities. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Cochlear implant; Residual hearing; Speech perception; Auditory deprivation; SENSORINEURAL HEARING-LOSS; PERFORMANCE; SURVIVAL; DURATION; DEAFNESS; AID